Open Radio Access Network (ORAN) Deployment Strategies for Remote Areas - Taiwo J. DURODOLA; Suleiman ZUBAIR; James AGAJO (FUDMA Journal of Engineering and Technology, 2026)
Extension of mobile coverage to sparsely populated rural and remote regions remain a global priority and presents unique challenges. This is due to the low population density; limited terrestrial backhauls and intermittent power associated with these regions. The disaggregation, open interfaces, RIC/SMO automation and potential cost-efficiencies of Open RAN promise architectural flexibility to improve economics and operations of Open RAN in rural and remote environments. This paper presents a systematic literature review of Open RAN deployment strategies in rural and remote areas. The review synthesizes academic studies, industry white papers, vendor/operator case reports and analyst studies. The literature supports strategies that include: (1) models that support infrastructure (Spectrum and Site) sharing integrated with renewable power sources and energy-aware features to manage OPEX and site autonomy (2) cloud-native DU/CU placement at regional edge sites combined with site local intelligence (RIC/SMO) for energy and radio optimization. (3) Hybrid backhaul using fiber/microwave for high-capacity node and satellite link or TVWS as backup or last-mile connection. Open RAN can make rural coverage more cost-effective when deployments are carefully designed using topology-aware functional splits, hybrid backhaul architectures, shared infrastructure models, robust SMO/RIC automation, and renewable energy solutions. Significant gaps persist in standardized TCO assessments and long-term, multi-vendor operational studies for rural and remote deployments.